Azerbaijan and diversionary war theory quantitative analysis - Sergoyan, Henrik; Martirosyan, Vahan; Bezirganyan, Grigor (YSU Journal of International Affairs, 2022)
The conflict between Armenia and Azerbaijan in Nagorno-Karabakh is one of the most intractable interstate in the Post-Soviet region. As such, analysis of the factors underlying the conflict has captured the attention of political scientists and pundits alike. Deemed largely a frozen conflict since the mid-1990s, speculations currently abound concerning reasons behind sporadic and large-scale flare-ups since 2015. One line of reasoning leverages the concept of “diversionary war theory,” which states that interstate warfare is often initiated by the incumbent leadership of at least one party to the conflict that is facing strong domestic pressure, with the goal of creating a rally around the flag effect and proving leadership competence. In particular, many posit that increasing fighting, most notably exemplified by the April 2016 clashes and the 44-day war in 2020, is a direct consequence of declining oil prices and the resulting economic woes in Azerbaijan. We set out to examine this theory using through a data scientific approach, employing proxy indicators for economic and social stability, oil price fluctuations, and diplomacy-warfare dynamics surrounding the Nagorno-Karabakh issue. Since the proliferation of mass media and advanced machine learning algorithms for natural language processing, we have the capacity to generate granular and nuanced insights concerning conflict dynamics, using open - source intelligence such as news or social media. As such, we leverage the Global Database of Events Language and Tone (GDELT) to quantify relative levels of diplomacy, warfare and social unrest. Our research shows a stark shift in the relationship between conflict dynamics and the economic situation in Azerbaijan before and after 2014. After 2014, warfare and diplomacy dynamics had a strong negative correlated with the difference between the breakeven oil price set by the government of Azerbaijan to balance its budget and the price of oil in international markets.
Keywords: Nagorno-Karabakh conflict; diversionary war theory; mass media; oil price; machine learning; natural language processing